Post-pandemic assessment of knowledge, attitude and practices of healthcare professionals regarding telemedicine: a pilot study - Kshirsagar, Minal M.; Clementina, Ruchira; Singhal, Rohan; Sandhu, Manpal Kaur; Bains, Arshjot Kaur; Khan, Usman; Patil, Aditi; Lakdawala, Zahabiya; Katta, Madhavi; Thokala, Hema; Yendluri, Suzanne Melissa; Lakhani, Alisha (International Journal of Research in Medical Sciences, 2025)
Background: The COVID-19 pandemic has accelerated the adoption of telemedicine as an alternative method of healthcare delivery, enabling patient care while minimising physical contact. In India, its use is growing, yet understanding healthcare professionals’ perspectives remains essential for effective integration. Methods: A cross-sectional survey was conducted among healthcare professionals working in India. Data were collected using an online questionnaire comprising 15 structured, self-administered, and closed-ended questions. The survey captured demographic details such as age, gender, and profession. Responses were tabulated and manually analysed to assess knowledge, attitudes, and practices regarding telemedicine. Results: Most participants (86.23%, n=238) reported being familiar with the concept of telemedicine, including knowledge of relevant applications, platforms, and professional training. A large majority (84.43%, n=233) agreed that telemedicine could reduce patient travel costs, thereby improving accessibility to healthcare services. Conclusion: The study indicates that telemedicine is perceived positively by healthcare professionals in India and has strong potential as a complementary tool in healthcare delivery. Its integration could enhance access, reduce costs, and improve patient convenience, particularly in underserved areas.